Eksistensi Penggunaan Mobile Banking Dalam Analisis Melalui Pengaruh Teknologi, Pengalaman, dan Keamanan - Putra, Edy Yulianto; Vanessa, Vanessa; Ariyanto, Hepy Hefri (Universitas Proklamasi 45, 2025)
The purpose of this study is to analyze the factors that influence the sustainability of mobile application usage using the Technology Adoption Model (TAM) approach. The variables studied include ease of use, user experience, affective experience, and security & privacy. Data was collected through a survey of mobile banking users and analyzed statistically using quantitative methods. The results of the study indicate that ease of use, user experience, affective experience, and application security and privacy significantly influence user satisfaction. User satisfaction then becomes a key factor that mediates the influence of these variables on the intention to continue using mobile banking. These findings show that the higher the level of user satisfaction, the greater the likelihood that users will continue to use mobile banking services. Additionally, security and privacy were proven to be fundamental aspects of user trust and loyalty. The implications of this study are the importance of developing mobile banking applications that are easy to use, provide a positive experience, and ensure the security and privacy of user data to increase user satisfaction and loyalty in a sustainable manner. This study is expected to serve as a reference for developers and digital banking service providers in designing service improvement strategies in the current digital era.